Protein Kinase A Alterations in Adrenocortical Tumors - Espiard, S.; Ragazzon, B.; Bertherat, J. (Hormone and Metabolic Research, 2014)
Stimulation of the cAMP pathway by adrenocorticotropin (ACTH) is essential for adrenal cortex maintenance, glucocorticoid and adrenal androgens synthesis, and secretion. Various molecular and cellular alterations of the cAMP pathway have been observed in endocrine tumors. Protein kinase A (PKA) is a central key component of the cAMP pathway. Molecular alterations of PKA subunits have been observed in adrenocortical tumors. PKA molecular defects can be germline in hereditary disorders or somatic in sporadic tumors. Heterozygous germline inactivating mutations of the PKA regulatory subunit RIα gene (PRKAR1A) can be observed in patients with ACTH-independent Cushing’s syndrome (CS) due to primary pigmented nodular adrenocortical disease (PPNAD). PRKAR1A is considered as a tumor suppressor gene. Interestingly, these mutations can also be observed as somatic alterations in sporadic cortisol-secreting adrenocortical adenomas. Germline gene duplication of the catalytic subunits Cα (PRKACA) has been observed in patients with PPNAD. Furthermore, exome sequencing revealed recently activating somatic mutations of PRKACA in about 40% of cortisol-secreting adrenocortical adenomas. In vitro and in vivo functional studies help in the progress to understand the mechanisms of adrenocortical tumors development due to PKA regulatory subunits alterations. All these alterations are observed in benign oversecreting tumors and are mimicking in some way cAMP pathway constitutive activation. On the long term, unraveling these alterations will open new strategies of pharmacological treatment targeting the cAMP pathway in adrenal tumors and cortisol-secretion disorders.
Keywords: cAMP; PKA; adrenal tumors; Cushing’s syndrome